PENYULUHAN KEBERSIHAN LINGKUNGAN DI DESA KREMBANGAN KECAMATAN GUDO KABUPATEN JOMBANG - Sudarwati, Ninik (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2025)
The environmental hygiene counseling program in Krembangan Village was motivated by the still low quality of sanitation and community waste management, which has an impact on the high risk of environmental-based diseases. This activity aims to improve community knowledge, attitudes, and behavior regarding the importance of maintaining environmental cleanliness in a sustainable manner. The implementation method includes the preparation phase, implementation of counseling, monitoring and evaluation, sustainability strategies, and strengthening community capacity. The approach used is participatory and contextual, through workshops, group discussions, simulations, and direct practice such as making healthy toilets and waste sorting systems. The results show an increase in awareness and active participation of residents, although challenges are still encountered in the form of limited infrastructure, cultural resistance, and low access to clean water. The formation of environmental cadres and integration of programs with village activities are the main strategies for maintaining sustainability. This counseling proves that collaboration between the community, local figures, and the village government is able to encourage changes in clean and healthy living behavior at the community level.